Application of Reverse Osmosis Membrane Technology in Trans Malakoni Village, Enggano Island - Ashar Muda Lubis; Fachruzzaman Fachruzzaman; Rini Indriani; Sipriyadi Sipriyadi; Darmawan Ikhlas Fadli (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Trans Malakoni Village, located on Enggano Island, Bengkulu Province, faces significant challenges in providing access to clean, potable water. Limited access to adequate freshwater sources and water quality that frequently fails to meet health standards are major obstacles to the community's sustainable livelihood. This research aims to explore the potential and implementation of household-scale reverse osmosis (RO) technology as an innovative solution for producing clean, potable water in Trans Malakoni Village. The research methodology involves raw water quality analysis, the design of a household-scale RO system suitable for local conditions, and an evaluation of system performance and community acceptance. Initial results indicate that existing water sources in Trans Malakoni Village, although limited, can be effectively treated using RO technology to achieve established drinking water quality standards. The proposed household-scale RO system design emphasizes energy efficiency, operational ease, and affordable maintenance costs, thereby enabling sustainable adoption by households. The implementation of RO technology is expected not only to enhance access to clean water but also to contribute to improved public health, self-reliance in water resource management, and sustainable living in Malakoni Village. This study recommends further research on system optimization and community education programs to maximize the positive impact of RO technology in other remote island regions.